Students’ Perception on Using Duolingo for Learning English Vocabulary - Anton Adi Purwanto; Syafryadin (Journal of English Teaching, 2023)
The rise of technology has expanded a variety of interesting and new online-based learning aids for English. Duolingo app, which makes learning languages, especially English, easy, accessible, and effective.The objective of this study is to describe and observe the students' perceptions of using Duolingo software for vocabulary at Madrasah Tsanawiyah 01 Darussalam Kepahiang. This study applied qualitative analysis techniques and conducted tests, questionnaires, and interviews as well as interviews to collect data. In this study, the writer used a non-probability sampling method in which 25 students from class VIII E were selected as a sample. This study found that the majority of students were encouraged to learn English vocabulary through this Duolingo application. Students can use the Duolingo app to learn English vocabulary which is easy to understand and students are more interested and excited about learning new words. Duolingo can also keep students from getting bored while learning and help them come up with new ways to learn. According to the findings of the research, it is possible to assume that students' perception of using Duolingo is positive and extremely helpful for enhancing vocabulary during learning English. Keywords: duolingo, students perception, vocabulary